Effects of Increasing Soybean Meal in Corn-Based Diets on Growth Performance of Late Finishing Pigs - Julia P. Holen; Robert D. Goodband; Mike D. Tokach; Jason C. Woodworth; Joel M DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2021)
A total of 1,793 pigs (L337 × 1050, PIC, Hendersonville, TN; initially 231.2 ± 2.4 lb) were used to evaluate the effects of increasing soybean meal in corn-based diets on growth performance of late finishing pigs. Pens of pigs were blocked by initial weight and randomly assigned to 1 of 5 dietary treatments with 22 to 27 pigs per pen and 12 to 14 pens per treatment. Experimental diets were corn-based, formulated to 0.70% SID Lys, and contained varying amounts of feed grade AA to meet or exceed requirement estimates. Soybean meal gradually increased from 5 to 20% of the diet and replaced feed grade AA. Thus, experimental diets contained 9.6, 10.8, 12.0, 13.4, or 14.7% CP. Pigs were weighed to evaluate ADG, ADFI, and F/G. Data were analyzed with the GLIMMIX procedure of SAS using pen as the experimental unit. The statistical model considered fixed effects of treatment, linear, quadratic, and cubic contrasts, and random effects of group and block. Overall, pigs fed increasing soybean concentrations in the late finishing period exhibited increased ADG (linear and cubic,P<0.05), and improved F/G (linear and cubic,P<0.05). The greatest improvements were observed as dietary soybean meal increased from 5 to 8.75% and from 16.25 to 20%. Additionally, final BW of pigs increased (cubic,P<0.05) as SBM increased from 5 to 8.75% and from 16.25 to 20%. Although diets were formulated to exceed the minimum NRC (2012) nutrient requirement estimates, we suspect the observed response may be due to the increased Trp:Lys ratio of 21.6 in the 20% SBM diet compared to 20% in all other diets. These results suggest that at least 8.75% soybean meal should be utilized to increase dietary CP content beyond 11% to improve growth performance of late finishing pigs in corn-based diets.
Keywords: amino acids; crude protein; finishing pigs; growth performance; soybean meal